Mitral valve repair using leaflet expansion and subpartial annuloplasty in childrenCentral MessagePerspective - Per Wierup, MD, PhD; Jens Johansson Ramgren, MD, PhD; Johan Sjögren, MD, PhD; Kiet Tran Phan, MD, PhD; Igor Zindovic, MD, PhD; Shahab Nozohoor, MD, PhD; Lea Christierson, MSc; Nina Hakacova, MD, PhD (JTCVS Techniques)
Objective: Mitral valve reconstruction in the pediatric population is a challenge due to the frequent combination of annular dilatation and leaflet restriction and the need for growth. We present a novel strategy using leaflet expansion and subpartial annuloplasty with polytetrafluoroethylene reinforcement. Methods: From January 2014 through May 2021, 11 children aged 5 months to 14 years (median, 24 months) underwent elective mitral valve repair due to severe mitral valve regurgitation. The mitral valve abnormalities included congenital malformations (n = 7), postoperative leakage following commissurotomy (n = 1), and functional mitral valve regurgitation due to dilated cardiomyopathy (n = 3). Surgery consisted of leaflet expansions with autologous, untreated pericardium and subpartial annuloplasty with polytetrafluoroethylene reinforcement. Results: All children survived their surgeries with uneventful postoperative courses, except for 1 patient who needed an early reoperation to resolve a functional stenosis due to a spinnaker phenomenon. At discharge, mean gradient was 3.5 ± 3.9 mm Hg, with trivial mitral regurgitation in 9 patients (82%). All patients were alive and asymptomatic during the median follow-up of 3 years (range, 1-7 years). Their echocardiographic data showed a mean transmitral gradient of 4.4 ± 1.7 mm Hg and remained unchanged. Residual mitral valve regurgitation was trivial or mild in 9 patients (82%) and moderate in 2 patients (18%). Conclusions: Leaflet expansion with autologous pericardium and subpartial annuloplasty with polytetrafluoroethylene reinforcement for mitral regurgitation in the pediatric population gives stable and satisfactory results both early and at intermediate follow-up, permitting growth of the mitral valve.